PKM SOSIALISASI PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DENGAN SHARING SESSIONS INTERAKTIF DI PONDOK PESANTREN - Novela Eka Candra Dewi; Putri Kurnia Dewi; Puput Divia Fitriani; Nurul Mustafidzah; Rukayyah Bahjatul (JURNAL SUAKA INSAN MENGABDI (JSIM), 2025)
Dengue Hemorrhagic Fever (DHF) is a significant health problem, especiallyin tropical areas such as Indonesia. The purpose of this community service is toincrease awareness and understanding of DHF prevention in Islamic BoardingSchools through interactive sharing sessions. The community service methoduses observation sheets to observe the behavior of students during and afteractivities that include Activeness in Discussion: How often students participatein discussions and Q&A. Application of Knowledge: How often students applythe knowledge gained in everyday life, such as cleaning the Islamic boardingschool environment. There was an increase in behavior in adolescents,especially in draining the bathtub and an increase in adolescent knowledge incontrolling DHF in the Islamic boarding school environment. Where, based onthe evaluation results, the majority (98%) had good knowledge related to DHFcontrol. The conclusion of this community service shows that interactive sharingsessions are effective in increasing awareness and knowledge about DHFprevention. The active participation of Islamic boarding school participants inthis session indicates that the interactive approach can be a successful model forcommunity service in the future, with a significant impact on reducing the riskof disease spread in the community.Keywords: DHF; Sharing Sessions; Socialization.